The evolution of money debate: Functionalism versus chartalism, Schumpeterian dynamics, Gresham's fallacy, and how history constrains public finance - Thomas I. Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
This paper discusses the evolution of money and the monetary system. The origins of money debate is framed in terms of functionalism versus chartalism. Endogenous Schumpeterian dynamics apply to the evolution of money and monetary systems, and those dynamics are supportive of the functionalist perspective. A functionalist Schumpeterian lens shows "Gresham's law" should be relabeled "Gresham's fallacy" because good money drives out bad. The Gresham dynamic is also supportive of the functionalist perspective. Lastly, the paper shows monetary history over the past millennium does not support chartalist public finance claims as represented by modern money theory (MMT).
Keywords: E4; E44; 330; Money; functionalism; chartalism; Gresham's law; Schumpeterian dynamics; modern monetary theory